A unique rhinologic manifestation of multiple myeloma - Jun Jie Seah; Wee Joo Chng; Mark Kim Thye Thong (Otolaryngology Case Reports, 2021)
Objectives: To describe unusual vascular lesions in the nasal mucosa of a patient with multiple myeloma (MM), presenting with recurrent epistaxis. Materials and Methods: An extensive literature review was done looking for previous reports describing epistaxis secondary to nasal mucosa abnormalities in patients with MM. Medical records of a patient with unusual mucosal vascular lesions, including her presenting symptoms, history and nasoendoscopic examination were reviewed. Nasoendoscopic images showing changes in the mucosal vascular lesions, before and after MM treatment, were compared. Results: To date, there are no reports describing nasal vascular lesions in MM patients, that is not otherwise attributable to another pathology. Our patient presented with vascular lesions in her nasal mucosa, causing recurrent bloodstained nasal secretions. With definitive treatment of MM with chemotherapy and stem-cell transplant, her nasal vascular lesions and epistaxis resolved alongside resolution of her MM. Conclusion: While vascular lesions in MM are described in other areas (eg. skin, retina), there are no reports describing any local nasal lesions not otherwise attributable to other pathophysiologies. Whether these lesions developed as part of the natural disease progress of MM is currently unclear. In patients with nasoendoscopy showing widespread raw granular mucosa or petechiae, and negative investigations (especially non-specific histology), we propose that MM be considered as a rare but possible differential diagnosis.